Supernatural Season 13 Disc 2 - Padalecki, Jared, 1982-; Ackles, Jensen; Collins, Misha; Warner Bros. Home Entertainment (Firm) (Burbank, CA Warner Bros. Home Entertainment, 2018)
Jack, the son of Lucifer and a powerful Nephilim, roams the earth with no idea of who or what he is and what havoc he can wreck, causing no small amount of tension between monster hunters Sam and Dean Winchester, as the brothers try to figure out what to do with him. Their angelic ally, Castiel, is out of reach and their mother Mary is trapped in an apocalyptic world with Lucifer. The Winchesters must reunite their family, rescue Castiel, and save the world from Lucifer ... again.
Title from disc surface.
Originally broadcast in 2017.
Wide screen.
Complete Season 13 contained on 5 disc set.
Jared Padalecki, Jensen Ackles, Misha Collins, Alexander Calvert, Samantha Smith, Mark Pellegrino.
Rating: Not rated CHV rating: 14A.
Keywords: Angels -- Drama; Devil -- Drama; Good and evil -- Drama; Supernatural -- Drama; Brothers -- Drama; Drama; Horror television programs; Video recordings for the hearing impaired